Self-Efficacy and Homesickness in UKSW Migrant Students from Bitung City - Sondakh, Jourdan Dirk; Soetjiningsih, Christiana Hari (International Journal Labs, 2023)
In this quantitative correlational research, the primary objective is to elucidate the relationship between self-efficacy and homesickness among a cohort of 77 UKSW migrant students hailing from Bitung City. The study employs a saturated sampling technique to ensure comprehensive participant representation. The research instrument integrates the well-established general self-efficacy scale (GSES), developed by Schwarzer and Jerusalem, and the homesickness questionnaire (HQ), crafted by Archer. Upon conducting data analysis using the Product Moment Pearson correlation technique, the study reveals a noteworthy correlation coefficient (rxy) of -0.671, accompanied by a significance value of 0.000 (p < 0.05). This statistical outcome signifies a significant negative relationship between self-efficacy and homesickness in UKSW migrant students from Bitung City. Essentially, the findings suggest that heightened levels of self-efficacy are associated with diminished experiences of homesickness. Conversely, lower levels of self-efficacy are linked to increased homesickness among this student cohort. This research sheds light on the pivotal role of self-efficacy in influencing the emotional well-being of international students, particularly in the context of homesickness. The implications extend to the development of targeted interventions and support strategies aimed at enhancing the overall resilience and adjustment of migrant students. Future research endeavors may delve deeper into additional factors influencing homesickness and explore effective intervention strategies to bolster self-efficacy, thereby addressing the multifaceted challenges faced by international students.